A Dipleiadiene‐Embedded Aromatic Saddle Consisting of 86 Carbon Atoms. Issue 6 (10th January 2018) - Pun, Sai Ho; Chan, Chi Kit; Luo, Jiye; Liu, Zhifeng; Miao, Qian
Abstract: This study presents a new type of negatively curved nanographene (C86 H32 ) that contains an unprecedented pattern of heptagons. A tert ‐butylated derivative of C86 H32 was successfully synthesized using tetrabenzodipleiadiene as a key building block. This synthesis involved a ring expansion reaction as a key step to form the seven‐membered rings in the framework of tetrabenzodipleiadiene. The single‐crystal structure reveals a saddle‐shaped molecule with a highly bent naphthalene moiety at the center of the polycyclic backbone. As found from the DFT calculations, this aromatic saddle is flexible at room temperature and has a saddle‐shaped geometry as the dominant conformation. The DFT calculations along with experimental results show that the attachment of t ‐butyl groups to the central tetrabenzodipleiadiene moiety of nanographene C86 H32 can stabilize the saddle conformation and make this nanographene less flexible. Abstract : Class of 86 : A type of negatively curved nanographene with an unprecedented pattern of heptagons in a polycyclic framework of 86 sp 2 carbon atoms was successfully synthesized with ring expansion as a key step. The saddle‐shaped π‐backbone was revealed by X‐ray crystallography, and its stereochemical dynamics were studied by DFT calculations. (Picture: substituents in crystal structure removed for clarity.)